PERILAKU KONSUMTIF MAHASISWI SUKU SUMBAWA DI PULAU LOMBOK: PERSPEKTIF INTERAKSIONISME SIMBOLIK - Novitasari Novitasari; Abdul Latif; M. Zainul Asror; Ahmad Tohri (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the forms of consumptive behavior and the factors influencing consumptive behavior among Sumbawanese female students pursuing higher education on Lombok Island, with particular attention to their experiences as migrant students and the role of social interaction. The study employed a qualitative approach with a descriptive design. Informants were selected purposively and consisted of nine Sumbawanese female students enrolled in higher education institutions on Lombok Island. Data were collected through in-depth interviews, observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and verification. Data credibility was strengthened through source and technique triangulation. The findings indicate that consumptive behavior is not limited to purchasing unnecessary goods but also takes the form of trend-oriented consumption, lifestyle consumption, peer-mediated purchasing, spontaneous buying, and the use of digital payment services. Social media, peer conformity, transaction convenience, lifestyle, and economic conditions operate as interrelated factors. As migrant students, the participants negotiate consumption practices associated with their home culture with consumption patterns encountered in their university and residential environments. From a symbolic interactionist perspective, commodities and consumption activities acquire social meanings through interaction, allowing consumption to function as a mechanism of social adjustment and identity presentation. These findings highlight the importance of financial literacy, self-control, and media literacy in fostering more reflective and rational consumption practices among university students.